Physical and Chemical Properties of Anodised Titanium in Sulphuric Acid for Biomedical Application - Selimin, Mohamad Ali; Te Chuan, Lee; Idris, Maizlinda Izwana; Abdullah, Hasan Zuhudi (International Journal of Integrated Engineering, 2018)
Fabrication of bioactive titanium (Ti) by using anodic oxidation method for biomedical application as a high-performance material with good biocompatibility properties has been introduced since many years ago. The current study aims to investigate the physical and chemical properties of anodised Ti oxide layer in sulphuric acid at different applied voltages. High purity Ti films were anodised with varying voltages (50-200 V) in 0.3 M of sulphuric acid at 75 mA.cm-2 current density for 10 min. Anodised Ti films were characterised for physical properties (colour, porosity, surface morphology, thickness) and chemical property (surface mineralogy). The anodised Ti produced using high voltage (200 V) appeared to be highly porous and demonstrated high crystallinity of rutile and anatase as well thicker oxide layer. From the results, the correlation between the physical and chemical properties can be used as a prediction of the properties of anodised Ti in sulphuric acid for a different parameter.